FUNGSI SATUAN POLISI PAMONG PRAJA DALAM PENERTIBAN PELACURAN DI KOTA KUPANG - Juan M.M. Ndun; Kotan Y. Stefanus; Cyrilius W.T. Lamatoro; Jeffry A. Ch. Likadja (PT. Hasba Edukasi Mandiri, 2026)
Prostitution is a form of social pathology that poses serious challenges to public order, social stability, and moral values. Within the framework of regional autonomy, local governments are authorized to address prostitution through regional regulations and administrative law enforcement carried out by regional apparatuses, particularly the Civil Service Police Unit (Satpol PP). In Kupang City, prostitution control is regulated by Regional Regulation Number 39 of 1999 concerning the Control of Prostitution Sites. This study aims to analyze the regulatory framework governing the functions of Satpol PP in controlling prostitution in Kupang City, examine the implementation of prostitution control measures, and identify factors that hinder the effectiveness of these functions. This research employs a normative-empirical juridical method using statutory and conceptual approaches. Data were collected through interviews, observations, and literature reviews. The findings indicate that although Satpol PP has implemented preventive and repressive measures, the control of prostitution has not been optimal. Major obstacles include weak regional regulations that are not responsive to modern forms of prostitution, limited human resources and budgetary support, and low levels of public legal awareness. The study concludes that effective prostitution control requires regulatory reform, institutional strengthening of Satpol PP, and more comprehensive and sustainable policy approaches.